Starting a Business Strategy for Prospective Entrepreneurs - Aseanty, Deasy; Warsindah, Lucy; Pakpahan, Arnolt; Didi, Didi; Triyani, Triyani (PT FORMOSA CENDEKIA GLOBAL, 2024)
Starting a business is an exciting yet challenging endeavor that requires careful planning, strategic thinking, and a clear understanding of the market. This activity explores effective startup strategies specifically designed for aspiring entrepreneurs who want to turn an innovative idea into a successful business. Key focus areas include market research, business model development, resource allocation, and leveraging digital tools for growth. This activity highlights the importance of identifying target audiences, minimizing risk through lean startup methodologies, and creating value-driven solutions to meet customer needs. This activity also emphasizes the role of networking, mentorship, and adaptability in navigating the dynamic business landscape. By adopting these strategies, aspiring entrepreneurs can increase their chances of building sustainable and scalable ventures while driving innovation and economic growth.